PERLINDUNGAN HUKUM BAGI PENJUAL MARKETPLACE AKIBAT KERUGIAN LAYANAN COD - Fathni, Indriya; Jauhari, Moh Ahsanuddin; Sulastri, Dewi; Najmudin, Nandang; Nurhayani, Neng Yani; Khoirunnisa, Saskia Fazrin (Universitas Muhammadiyah Ponorogo, 2023)
Increasingly advanced technology does not always have a positive impact, sometimes it has a negative impact. This is like a widespread case because of the development of the Shopee marketplace which provides Cash On Delivery services) which, instead of benefiting the seller, is detrimental. This loss is not the responsibility of Shopee, but the seller itself. However, there is relevance to positive laws and regulations in Indonesia that can resolve this case. This study's goal is to determine the type of legal protection available to seller viewed from the Consumer Protection Act, the ITE Law, and the Civil Code and to find out Shopee's responsibility in protecting sellers who lose money because of the COD service. A technique to study called normative juridical is applied. The approach used is the legal approach. The data collection technique used is literature study. The data and data sources used come from secondary data, namely research journals, laws, and electronic sources that can be accounted for. The results and analysis of this study are that the regulations contain Law no. 8 of 1999 concerning Consumer Protection Articles 5, 6, 7, 34 and 45; Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions Article 45A; and the Civil Code Articles 1513, 1514, 1517, 1243, and 1267. Then, efforts to resolve this case can be done either through or outside the court and the seller activates the shipping insurance provided by Shopee.